2013
DOI: 10.1002/csr.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedents of Corporate Social and Environmental Irresponsibility

Abstract: This study combines internal and external perspectives to examine the antecedents of corporate social and environmental irresponsibility. In terms of internal factors, we focus on the extent to which a firm incorporates corporate social responsibility (CSR) into its business strategy and the level of firm-specific R&D investment. With respect to external factors, we focus on market cost pressure and local government corruption. We developed hypotheses and tested them using original survey data of 295 Chinese f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 61 publications
2
38
0
7
Order By: Relevance
“…Firmalar doğru yapılandırılmış, etkin bir ölçme ve öz-denetim sisteminin var olması durumunda çevresel performanslarını daha hızlı iyileştirebilmektedir [19,20]. Chih vd.…”
Section: Firma Performansı Ve çEvresel Performansın öLçülmesiunclassified
See 1 more Smart Citation
“…Firmalar doğru yapılandırılmış, etkin bir ölçme ve öz-denetim sisteminin var olması durumunda çevresel performanslarını daha hızlı iyileştirebilmektedir [19,20]. Chih vd.…”
Section: Firma Performansı Ve çEvresel Performansın öLçülmesiunclassified
“…Çevresel performansın öneminin anlaşılmasına paralel olarak Türk inşaat sektöründe faaliyet gösteren çeşitli meslek örgütleri ve ulusal araştırma kuruluşları da yüklenici firmaları çevresel performanslarını iyileştirmeye teşvik etmiştir [14,15,16,17,18]. Firmalar doğru yapılandırılmış, etkin bir ölçme ve öz-denetim sistemi ile çevresel performanslarını daha hızlı iyileştirebilmektedir [19,20]. Firmanın faaliyet alanına, içinde bulunduğu çevreye ve amaçlarına uygun sistem ve göstergeler kullanılması, firmanın uygun hedeflere doğru yönlendirilmesi ve performans ölçümünün hedefine ulaşabilmesi bakımından son derece önemlidir [21].…”
Section: Introductionunclassified
“…Rather, we believe that the failure to respect a negative duty (i.e., doing no harm) cannot be compensated by a positive duty or action in favour of the affected (or other) constituencies (i.e., doing good). Thus, following prior research (e.g., Fiaschi, Giuliani, & Nieri, 2015, 2017Strike, Gao, & Bansal, 2006;Surroca, Tribo, & Zahra, 2013;Wu, 2014), we treat CSIR and CSR as two conceptually and empirically distinct constructs. sometimes criticised for allowing firms to show only the good side of their activities (Morsing, 2017) in a bid to gain and maintain external legitimacy (Bansal & Kistruck, 2006;Dhaliwal, Li, Tsang, & Yang, 2011;Nikolaeva & Bicho, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Enterprises have been criticized for irresponsible behaviors such as contaminating the environment, exploiting labor, cheating consumers, and causing damage to suppliers . Wu (2014) reported that cost pressure and government corruption are two major factors affecting the possibility of enterprises practicing socially irresponsible behaviors. In other words, enterprises lose customers when they increase the price of a product, and this compels them to reduce their costs (i.e., reduce the personnel cost or jerry-build products) to maintain the price; such cost reduction can stimulate additional irresponsible behaviors.…”
Section: Csr and Csirmentioning
confidence: 99%
“…Taneja et al (2011) categorized CSR research into five major types. Type one discussed the meaning, definition, and model of CSR (Carroll, 1979(Carroll, , 1999(Carroll, , 2010Dahlsrud, 2008;Van Marrewijk, 2003); type two identified factors determining CSR (Lange & Washburn, 2012;Wu, 2014); type three analyzed actions of CSR (Oberseder, Schlegelmilch, & Murphy, 2013;Babiak & Trendafilova, 2011;Bravo, Matute, & Pina, 2012); type four identified the effects of CSR on stakeholders and financial performance (Chih et al, 2014;Lombart & Louis, 2014;Lu, Chau, Wang, & Pan, 2014;Oberseder et al, 2013); type five explored the measurement tools of corporate social performance (Giannarakis, Litinas, & Theotokas, 2011;Turker, 2009;Wood, 2010;Wagner, Bicen, & Hall, 2008). Extensive research has been conducted on CSR; however, little research has addressed the concerns of CSR (i.e., CSiR), which is a major gap in consumer behavior research.…”
Section: Csr and Csirmentioning
confidence: 99%